Probability and Statistics A Course for Physicists and Engineers - Mathai, Arak M. (De Gruyter Textbook, 2017)
This textbook offers an introduction to concepts of probability theory, probability distributions relevant in the applied sciences, as well as basics of sampling distributions, estimation and hypothesis testing. As a companion for classes for engineers and scientists, the book also covers applied topics such as model building and experiment design.